Study of nitrogen and phosphorus nutrient dynamics in concentrated marine fish farming water environment in Long Son - Vung Tau - Tran, Quang Thu; Nguyen, Duc Cu (Vietnam Journal of Marine Science and Technology, 2024)
The nutritional content of N and P in concentrated marine fish farming water in the Cha Va - Long Son - Vung Tau estuary area increased sharply during 2013–2016; notably, the N-NH4+ content increased in 2017–2019. The N-NO2- and N-NO3- content in the dry season (0.051 mg/L and 0.190 mg/L) was higher than in the rainy season (0.044 mg/L and 0.133 mg/L). In contrast, the N-NH4+ and P-PO43- contents in the rainy season (0.321 mg/L and 0.1 mg/L) are higher than in the dry season (0.154 mg/L and 0.093 mg/L). The N and P nutrient dynamics in water fluctuate according to the semi-diurnal tide regime; the nutrient content decreases during high water - daytime, increases during low water in the evening, and is high during high water at night and in the morning, early the next day. In dry and rainy seasons, the N-NH4+ content is always the highest (0.024–0.761 mg/L) among the nitrogen-based nutritional parameters. N and P nutrients in water are correlated: N-NH4+ parameter pairs with Total P, N-NO2- with Total P, Total N with Total P, N-NO2- and N-NO3-, P-PO43- with Total P, and the parameter pair N-NO2- with P-PO43- have low positive correlation coefficients (r), from 0.1–0.21. Conversely, the parameter pairs N-NO3- and Total N, N-NO3- and N-NH4+, and N-NO2- and N-NH4+ have low negative correlation coefficients (r), from -0.12 to -0.26. From 2010–2021, the number of cages increased beyond planning, causing environmental pollution in the water in the farming area. The nutritional RQ value of the water is high at level 4 every year (very high risk of environmental pollution).